2020
DOI: 10.1038/s41598-020-61913-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of soybean nodulation by seed treatment with non–thermal plasmas

Abstract: Soybean (Glycine max (L.) Merrill) is one of the most important crops worldwide providing dietary protein and vegetable oil. Most of the nitrogen required by the crop is supplied through biological n 2 fixation. Non-thermal plasma is a fast, economical, and environmental-friendly technology that can improve seed quality, plant growth, and crop yield. Soybean seeds were exposed to a dielectric barrier discharge plasma operating at atmospheric pressure air with superimposed flows of O 2 or n 2 as carrying gases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 52 publications
4
69
0
Order By: Relevance
“…Decreased content of daidzein, genistein, and daidzin in roots of soybean seedlings has been determined previously, [ 28 ] while according to results, the amounts of many flavonoids were increased in red clover root exudates (Figure 4). It is pertinent to note that the amounts of compounds exuded to rhizosphere depend not only on their biosynthesis and their content in the root but also on the diverse proteins mediating their sequestration, release, and transport, [ 46,47 ] such as passive transport systems and active systems, including ABC‐transporters, as well as apoplastic β‐glucosidases, which release isoflavones from their conjugates making them available for transport.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Decreased content of daidzein, genistein, and daidzin in roots of soybean seedlings has been determined previously, [ 28 ] while according to results, the amounts of many flavonoids were increased in red clover root exudates (Figure 4). It is pertinent to note that the amounts of compounds exuded to rhizosphere depend not only on their biosynthesis and their content in the root but also on the diverse proteins mediating their sequestration, release, and transport, [ 46,47 ] such as passive transport systems and active systems, including ABC‐transporters, as well as apoplastic β‐glucosidases, which release isoflavones from their conjugates making them available for transport.…”
Section: Resultssupporting
confidence: 70%
“…Soybean seeds were inoculated with nitrogen‐fixing Bradyrhizobium strain before sowing and used to grow seedlings in sterilized vermiculite. [ 28 ] We found that the number of root nodules increased after red clover seed treatment with CP and EMF, although we did not inoculate seeds and the seedlings were grown in multipurpose potting substrate; thus, nodular rhizobacteria originated either from red clover seeds or from the substrate, as they would in natural conditions. We did not observe any substantial effects on the growth of the above‐ground part of young (5‐week‐old) plants in this study, but we suppose that a large increase in red clover biomass production obtained after 5 months [ 20 ] can be explained by CP‐ and EMF‐stimulated nodulation and nitrogen fixation activity.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In practice, various types of seeds treatment are used, such as heating, exposure to high frequency currents, etc. [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%